Does the time of the day affect multiple trauma care in hospitals? A retrospective analysis of data from the TraumaRegister DGU® - Stefanie Fitschen-Oestern (BMC, 2021)
Abstract Background Optimal multiple trauma care should be continuously provided during the day and night. Several studies have demonstrated worse outcomes and higher mortality in patients admitted at night. This study involved the analysis of a population of multiple trauma patients admitted at night and a comparison of various indicators of the quality of care at different admission times. Methods Data from 58,939 multiple trauma patients from 2007 to 2017 were analyzed retrospectively. All data were obtained from TraumaRegister DGU®. Patients were grouped by the time of their admission to the trauma center (6.00 am–11.59 am (morning), 12.00 pm–5.59 pm (afternoon), 6.00 pm–11.59 pm (evening), 0.00 am–5.59 am (night)). Incidences, patient demographics, injury patterns, trauma center levels and trauma care times and outcomes were evaluated. Results Fewer patients were admitted during the night (6.00 pm–11.59 pm: 18.8% of the patients, 0.00–5.59 am: 4.6% of the patients) than during the day. Patients who arrived between 0.00 am–5.59 am were younger (49.4 ± 22.8 years) and had a higher injury severity score (ISS) (21.4 ± 11.5) and lower Glasgow Coma Scale (GCS) score (11.6 ± 4.4) than those admitted during the day (12.00 pm–05.59 pm; age: 55.3 ± 21.6 years, ISS: 20.6 ± 11.4, GCS: 12.6 ± 4.0). Time in the trauma department and time to an emergency operation were only marginally different. Time to imaging was slightly prolonged during the night (0.00 am–5.59 am: X-ray 16.2 ± 19.8 min; CT scan 24.3 ± 18.1 min versus 12.00 pm- 5.59 pm: X-ray 15.4 ± 19.7 min; CT scan 22.5 ± 17.8 min), but the delay did not affect the outcome. The outcome was also not affected by level of the trauma center. There was no relevant difference in the Revised Injury Severity Classification II (RISC II) score or mortality rate between patients admitted during the day and at night. There were no differences in RISC II scores or mortality rates according to time period. Admission at night was not a predictor of a higher mortality rate. Conclusion The patient population and injury severity vary between the day and night with regard to age, injury pattern and trauma mechanism. Despite the differences in these factors, arrival at night did not have a negative effect on the outcome.